PENGARUH AUDIT QUALITY DAN INDEPENDENSI AUDITOR TERHADAP MANAJEMEN LABA RIIL MELALUI FINANCIAL DISTRESS - Alma Maria Octavia; Husnah Nur Laela Ermaya; Dewi Darmastuti (Jurnal Ekonomi Dan Bisnis, 2022)
This research investigates the effect of audit firm size and auditor industry specialization that proxies audit quality, and auditor independence on real earning management through financial distress as an intervening variable. This study used 96 samples of manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2019 research period with a purposive sampling method. By using the Structural Equation Model, the results show that auditor industry specialization and auditor independence have a positive effect on real earnings management through financial distress. Conclusions from the the results of the study explain that financial distress can be a motivation for management to did real earnings management so that it can be an indication for auditor to detect real earnings management. Financial distress can motivate management to use their flexibility to modifiy company profit, so that it requires high quality of audit and independence of auditor. The result of this research are related to role and performance of auditor for understanding client’s condition and detecting irregularities, so this research contributes to examine audit quality and independence of auditor to detect real earning management through financial distress condition